Hubungan Kekuatan Otot Lengan dan Fleksibilitas Otot Punggung terhadap Efektivitas Teknik Koshi Guruma - Muhammad Alifi Irsyadillah; Arif Setiawan (MAN Insan Cendekia Jambi, 2026)
This study aimed to examine the relationship between arm muscle strength and back muscle flexibility and the effectiveness of the koshi guruma technique among judo athletes. A quantitative approach with a correlational research design was employed. The study involved 20 athletes from Nararya Sport Club Semarang who were selected through purposive sampling based on predetermined criteria. Data were collected using a push-up test to assess arm muscle strength, a V sit-and-reach test to measure back muscle flexibility, and a koshi guruma skill test to evaluate the effectiveness of technique execution. The collected data were analyzed using Spearman Rank correlation and multiple correlation analyses. The findings revealed a significant positive relationship between arm muscle strength and the effectiveness of the koshi guruma technique, as indicated by a correlation coefficient of 0.517 and a significance level of 0.020 (p < 0.05). In contrast, back muscle flexibility did not show a statistically significant relationship with the effectiveness of the technique, with a correlation coefficient of 0.318 and a significance value of 0.172 (p > 0.05). Furthermore, the results of the multiple correlation analysis demonstrated a significant simultaneous relationship between arm muscle strength and back muscle flexibility and the effectiveness of the koshi guruma technique, with an R value of 0.544 and a significance level of 0.039 (p < 0.05). The coefficient of determination (R²) was 0.296, indicating that the two independent variables jointly accounted for 29.6% of the variance in the effectiveness of the koshi guruma technique, while the remaining 70.4% was attributed to other factors beyond the scope of the study.